Effects of a 1-Year Physical Activity Intervention on Markers of Hemostasis among Breast Cancer Survivors: A Randomized Controlled Trial - Bøhn, Siv Kjølsrud; Thune, Inger; Flote, Vidar Gordon; Frydenberg, Hanne; Bertheussen, Gro Falkenér; Husøy, Anders; Fjeldheim, Frøydis; Brunvoll, Sonja Hjellegjerde; Hjartåker, Anette; Mowinckel, Marie-Christine; Sandset, Per Morten; Iversen, Per Ole (TH Open, 2021)
Introduction Physical activity may reduce the development of breast cancer. Whereas hypercoagulability has been linked to adverse outcomes in breast cancer patients, the effects of physical activity on their hemostatic factors are unknown. The study aimed to assess whether long-term (1 year) physical activity can affect hemostatic factors in breast cancer patients.Methods Fifty-five women (35–75 years) with invasive breast cancer stage I/II were randomized to a physical activity intervention (n = 29) lasting 1 year or to a control group (n = 26), and analyzed as intention to treat. Fibrinogen, factor VII antigen, tissue factor pathway inhibitor, and von Willebrand factor (VWF) antigen as well as prothrombin fragment 1 + 2, the endogenous thrombin potential and D-dimer, were measured in plasma before intervention (baseline), and then after 6 and 12 months.Results Maximal oxygen uptake (measure of cardiorespiratory fitness) decreased the first 6 months among the controls, but remained stable in the intervention group. We found no significant differences between the two study groups regarding any of the hemostatic factors, except a significantly higher increase in factor VII antigen in the intervention group. The effect of the intervention on VWF was, however, significantly affected by menopausal stage, and a significant effect of the intervention was found on VWF among postmenopausal women, even after adjustment for dietary intake.Conclusion Long-term physical activity had no effect on the majority of the hemostatic factors measured, but led to increased plasma concentrations of factor VII antigen and prevented an increase in VWF concentration after breast cancer treatment in postmenopausal women. The clinical impact of these findings for risk of vascular thrombosis warrants further studies.
Keywords: Breast Neoplasms; hemostasis; physical activity; postmenopause; von Willebrand factor